Anexos:
![](https://pt-static.z-dn.net/files/d6e/a136bb425b5e9eb44a5a03565e9df2eb.jpg)
Soluções para a tarefa
Respondido por
2
12 - 2 * (-6) / 3 * (-8)
= 12 - (-12) / -24
= 12 + 12 / - 24
= + 24 / -24
= -1
= 12 - (-12) / -24
= 12 + 12 / - 24
= + 24 / -24
= -1
albertrieben:
se gostou da minha resposta, escolha como a melhor
Respondido por
1
Boa tarde
(12 - 2*(-6))/(3*(-8))
= (12 + 12)(-24) = -24/24 = -1
(12 - 2*(-6))/(3*(-8))
= (12 + 12)(-24) = -24/24 = -1
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Administração,
1 ano atrás